2014
DOI: 10.1371/journal.pone.0090480
|View full text |Cite|
|
Sign up to set email alerts
|

Energy-Optimal Electrical-Stimulation Pulses Shaped by the Least-Action Principle

Abstract: Electrical stimulation (ES) devices interact with excitable neural tissue toward eliciting action potentials (AP’s) by specific current patterns. Low-energy ES prevents tissue damage and loss of specificity. Hence to identify optimal stimulation-current waveforms is a relevant problem, whose solution may have significant impact on the related medical (e.g. minimized side-effects) and engineering (e.g. maximized battery-life) efficiency. This has typically been addressed by simulation (of a given excitable-tiss… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
20
0
1

Year Published

2015
2015
2020
2020

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(25 citation statements)
references
References 27 publications
0
20
0
1
Order By: Relevance
“…Krouchev et al (2014) used the Least Action Principle and a space clamped patch of neuronal membrane to determine the optimal trajectory of transmembrane potential and subsequently, for a given model, determine the energy optimal stimulation current to drive the transmembrane potential along that trajectory. Again, the resulting optimal current waveforms were approximately Gaussian in shape, reinforcing the findings of earlier studies that fortuitously selected this shape a priori or arrived at this shape via optimization.…”
Section: Optimized Pulse Shapes For Stimulationmentioning
confidence: 99%
“…Krouchev et al (2014) used the Least Action Principle and a space clamped patch of neuronal membrane to determine the optimal trajectory of transmembrane potential and subsequently, for a given model, determine the energy optimal stimulation current to drive the transmembrane potential along that trajectory. Again, the resulting optimal current waveforms were approximately Gaussian in shape, reinforcing the findings of earlier studies that fortuitously selected this shape a priori or arrived at this shape via optimization.…”
Section: Optimized Pulse Shapes For Stimulationmentioning
confidence: 99%
“…Following the findings of recent computational studies on energy optimal stimulation waveforms [19]- [21], Gaussian shaped stimuli were compared against standard rectangular stimulation in a nerve-muscle preparation in anaesthetized rats in terms of energy, charge and power efficiency. In order to attain results that can be applied for practical applications such as cochlear implants or neuromuscular prosthetics, both commonly-used electrode configurations, monopolar and bipolar stimulation, were tested.…”
Section: Discussionmentioning
confidence: 99%
“…Promisingly, three recent studies independently found a Gaussian shaped stimulation waveform to be optimal in terms of minimized energy consumption using model-based approaches probed by a genetic algorithm [19], the calculus of variation [20] and the least action principle [21]. While these studies agree that a Gaussian stimulation waveform shows increased energy efficiency over rectangular stimuli, there are considerable differences in the claimed potential to save energy by replacing simple rectangular waveforms with modified pulses.…”
Section: Introductionmentioning
confidence: 99%
“…�is is illustrated in figure 10. Some examples include the genetic algorithm-based method of Wongsarnpigoon and Grill [39], the least-action principle pulses of Krouchev et al [40], and the patient-specific waveform synthesis of Yalçinkaya and Erbaş [41]. An important goal of such work is the minimization of pulse energy (thus obtaining extended battery life) while maximizing physiological efectiveness [42].…”
Section: Waveform Fidelitymentioning
confidence: 99%